Family Dynamic and Family Business Financial Performance: Spousal Commitment - Van Auken, Howard; Werbel, James (Family business review, 2006)
This article views the survival of a family business as partially dependent on spousal commitment. The decision to launch a business should depend not only on analysis of the opportunity, but also on the degree to which one's spouse shares a common vision about the goals, risks, and rewards of the business. Models and testable hypotheses are developed to guide empirical research on the antecedents and consequences of spousal commitment to a family business. The models can benefit individuals considering the launch of a business, couples that currently own a business, business consultants, and university instructors teaching entrepreneurship courses.